Analisis Strategi Marketing Public Relations PT. Bank Rakyat Indonesia (Persero) tbk dalam Meningkatkan Pengguna Kartu Brizzi - Rosyadi, Muhamad Imron (Universitas Muhammadiyah Yogyakarta, 2018)
AbstractMarketing Public Relations Strategy of PT. Bank Rakyat Indonesia (Persero) Tbk Branch Office of Yogyakarta in improving BRIZZI Card users.The results of this research showed that the public relations marketing program in increasing the number of BRIZZI card users performed special event programs, sponsorship, BRIZZI Trans Jogja, direct presentations, telemarketing, exhibitions event, advertising strategy, bundling, and BRIZZI co-branding or cooperation and also supported with various roles and functions performed by PT. Bank Rakyat Indonesia (Persero) Tbk Branch Office of Yogyakarta. The conclusion can be seen from the increasing number of BRIZZI card users in October which far exceeded the target. The implementation of marketing public relations program would be maximal again if supported by the role of the optimal marketing media, through concerted media (centralize activities on the media) in order that the publication can be realized with the maximum. Using concerted media, PT. Bank Rakyat Indonesia (Persero) Tbk Branch Office of Yogyakarta can attract customers to reach the target and of course will make the increase of BRIZZI card users.